Content Management Systems Functionality - Mateljan, Vladimir; Šimović, Vladimir; Juričić, Vedran (2008)
The paper analyzes today's content management systems in order to find the characteristics that are common to the majority of those systems, and to find what characteristics make them suitable for usage in online education. Authors analyzed great number of content management systems and their characteristics, and made a comparison of content management systems based on supporting operating systems, approximate cost and popularity.
Projekt MZOS
Projekt MZOS
ENG